Optimal choice of health and retirement in a life-cycle model - Michael Kuhn; Stefan Wrzaczek; Alexia Prskawetz; Gustav Feichtinger (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2012)
We examine within a life-cycle set-up the simultaneous choice of health care and retirement (together with consumption), when health care contributes to both a reduction in mortality and in morbidity. Health tends to impact on retirement via morbidity, determining the disutility of work, and through longevity, determining the need to accumulate retirement wealth. In contrast, the age of retirement drives health through changes in the value of survival and the value of morbidity reductions. We apply our model to analyse the effects of moral hazard in the annuity market: While moral hazard always induces excessive health investments and an excessive duration of working life it also triggers an excessive level of consumption if the impact of health on the disutility of work is sufficiently large. We examine a transfer scheme and mandatory retirement as policies to curtail moral hazard. Numerical analysis illustrates the working of our model.
Keywords: D91; I12; J26; 330; annuities; demand for health; moral hazard; life-cycle-model; optimal control; retirement; value of life